Studying the Impact of Management of Central Bank’s Monetary Policy Instability on Total Return of Tehran Stock Exchange - Roya Aleemran; seyed ali aleemran (راهبرد مدیریت مالی, 2014)
The Objective of this research is studying the impact of management of central bank’s monetary policy instability on total return of Tehran stock exchange from the first quarter of 1998 to the fourth quarter of 2011. For this purpose, first, the instability index of monetary policy is estimated using EGARCH model and then the impact of central bank’s monetary policy instability on total return of Tehran’s stock exchange has been examined using Johansen-Juselius method. The results of the model indicate that the impact of central bank’s monetary policy instability, coin price, land price index and interest rate on total return of Tehran’s stock exchange have been significantly negative, while central bank’s expansionary monetary policy and gross domestic production have significant positive impact on economic growth. Also, the results based on vector error correction model indicate that each period (a quarter), about 0.01 of short term imbalances is adjusted to achieve long term balance.